INHIBITED FACTORS IN MANAGEMENT GOVERNMENT FINANCE OF NAGARI: CASE STUDY IN NAGARI KAMANG HILIR, KAMANG MAGEK SUBDISTRICT, AGAM REGENCY - Vaguita, Mercya; Adnan, M. Fachri (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
The purpose of this study was to determine the inhibiting factors in the management government finance of Nagari in 2018, especially in the Nagari Government Budget (APB Nagari) in Kamang Magek District, Agam Regency, West Sumatra Province, namely Nagari Kamang Hilir. This study uses qualitative methods with descriptive analysis. The technique of collecting data using the interview approach consisted of 8 informants (Section of Financial Development and Wealth of Nagari DPMN, Financial and Development Management Section of Nagari DPMN, Secretary of Sub-District Head, Guardian of Nagari, Secretary, Treasurer, Head of Planning, Head of Government, and Bamus Nagari), focus group discussion (FGD) consisted of 5 informants (Wali Nagari, Secretary, Bamus, KAN, Youth, and Wali Jorong), and documentation studies. The results showed that the inhibited factors in management government finance of Nagari are still not following Permendagri Number 113 of 2014. There are inhibited factors in management government finance of Nagari including less supportive human resources, low community self-help, public oversight is still lacking, community participation is still low, and there is a change in the budget for reporting accountability.